Constructive Problems in Competitions in Mathematics and Computer Science - Чухнов, Антон Сергеевич (Computer Tools in Education, 2018)
Constructive problems arise in all areas of mathematics. They are very important in working with schoolchildren and students, as they are one of the easiest ways to stimulate students’ productive activities. This work is devoted to the role of constructive tasks in remote olympiads in mathematics and computer science. Also tasks of this kind can be used to monitor the intellectual activity of students in the educational process.